2022
DOI: 10.1111/1759-7714.14459
|View full text |Cite
|
Sign up to set email alerts
|

Different CT slice thickness and contrast‐enhancement phase in radiomics models on the differential performance of lung adenocarcinoma

Abstract: Background To investigate the effects of computed tomography (CT) reconstruction slice thickness and contrast‐enhancement phase on the differential diagnosis performance of radiomic signature in lung adenocarcinoma. Methods A total of 187 patients who had been pathologically confirmed with lung adenocarcinoma and nonadenocarcinoma were divided into a training cohort (n = 149) and validation cohort (n = 38). All the patients underwent contrast‐enhanced CT and the images were reconstructed with different slice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Firstly, the CT thickness utilized was 5 mm due to the extended time span. Despite previous studies indicating that different CT section thicknesses do not affect the discriminatory ability of radiomics models [ 29 , 30 ], prospective studies could be conducted in the future, with a focus on radiomics analysis using thin-slice CT scans. However, on the premise of ensuring the stability and accuracy of the model, we chose 5 mm CT thickness, which is consistent with other reports [ [31] , [32] , [33] , [34] ], and can reduce the workload of tumor delineation and improve operability.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the CT thickness utilized was 5 mm due to the extended time span. Despite previous studies indicating that different CT section thicknesses do not affect the discriminatory ability of radiomics models [ 29 , 30 ], prospective studies could be conducted in the future, with a focus on radiomics analysis using thin-slice CT scans. However, on the premise of ensuring the stability and accuracy of the model, we chose 5 mm CT thickness, which is consistent with other reports [ [31] , [32] , [33] , [34] ], and can reduce the workload of tumor delineation and improve operability.…”
Section: Discussionmentioning
confidence: 99%
“…Aerts et al 23 demonstrated that radiomics could differentiate the prognosis of different pathological subtypes of lung adenocarcinomas. Wang et al 24 showed that chest contrast-enhanced CT imaging could be used to identify lung adenocarcinoma. In this study, the models for the prediction of multiple primary invasive lung adenocarcinomas were established based on CT radiomics.…”
Section: Oc Curves Of the Ve Classi Cation Learners To Predict The Re...mentioning
confidence: 99%